Assessment of foliar application of nutrients on yield and quality of guava (Psidium guajava) - BALODA, SATPAL; SHARMA, JEET RAM; SHARMA, SUSHIL; MALIK, ARVIND; PRINCE; TOKAS, JAYANTI; Akshay Mehta (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during rainy (kharif) seasons of 2020–2022 at CCS Haryana Agricultural University, Hisar, Haryana to assess the effect of foliar application of nutrients on the yield and quality aspects of rainy season guava (Psidium guajava L.). Experiment was conducted in a randomized block design (RBD) comprised of 4 different foliar applications of zinc sulphate, viz. ZnSO4 @0% (Control); ZnSO4 @0.3%; ZnSO4 @0.6%; ZnSO4 @0.9%; and 4 foliar applications of potassium sulphate, viz. K2SO4 @0% (Control); K2SO4 @1.0%; K2SO4 @1.5%; and K2SO4 @2.0, and replicated thrice. However, foliar application of ZnSO4 @0.9% was found to be the best treatment in improving the fruit yield (46.2 kg/plant), fruit weight (135.2 g), fruit length (6.10 cm) and fruit breadth (5.64 cm) of rainy season guava (cv. L-49). Similarly, ZnSO4 @0.6% was found best for increasing the TSS (total soluble solids) (10.6 B) and ascorbic acid content (187.4 mg/100 g pulp). On the other hand, K2SO4 @2.0% increased the fruit yield (45.4 kg/plant), fruit weight (135.2 g) and ascorbic acid content (190.3 mg/100 g pulp) of guava fruit. The maximum N, P, K and Zn content for nutrient analysis in leaf was noted under foliar application of ZnSO4 @0.9% and K2SO4 @2.0%. The maximum N and Zn content in fruit was observed due to application of ZnSO4 @0.9% and maximum P and K content was observed with treatment ZnSO4 @0.6%. Similarly, K2SO4 @2.0% increased the N, P, K and Zn content of guava fruit.